Społeczno-gospodarcze przesłanki pracy zawodowej kobiet - Przedpelski, Mieczysław (Wydział Prawa i Administracji UAM, 1967)
The criteria of systematization of factors concerning the activization of women's work can be selected as a result of accepting many possible assumptions. If we accept as the proper criterium the relation with a strictly defined economic system, then the division thus arrived at will comprise two groups of factors, namely factors functioning irrespectively of the economic system and factors characteristic for that specific system. To the first group belong the deepening of the social division of labour and all its consequences. In that group finds itself also the technical progress, as the result of human thought. To the factors characteristic for concrete economic systems belongs the set of political decisions, undertaken by economic authorities, which are typical for that particular system. The second factor connected with a concrete system represent the decisions undertaken by members of the society, in the labour sphere. The deepening of the socialdivision of labour: This is a process which is immanent to many formations and still more numerous economic systems. The analysis of that problem leads one to believe, that the social, as well as the conrete and individual division of labour in the last effect prepare conditions which are propitious for women's work. However, these conditions demand that a special material basis exist for the social division of labour. The trends in the development of technicalprogress: The results of the study show, that each type of technical progress contributes to greater vocational activités of the female population. In the concrete economic system, on the other hand, this depends on the macroeconomic preferences aiming at the realization of a specific technical progress and a strictly defined engagement of the female labour force. The political decisions of economic authorities: This factor has to do with the social-economic practice. Its analysis permits to put forward a thesis according to which the political decisions concerning the women's work should be based on broader foundations — and not only on foundations laid by one scientific discipline, Lex. economics. The goal after which the decisions should strive is to fulfill human endeavours and ambitions. They should at the same time influence and direct those endeavours and ambitions, draw attention to unconscious alternatives, stir critical attitudes and comments with regard to traditional „values", which are incompatible with new tendencies of the social, economic, political and cultural development. Decisions of members of society: That problem is of great significance from the point of view of quantitative and qualitative side of the social labour process. The crux of that matter consists in the global supply of labour force, and is thus conditioned by natural and social factors. The decision to take part in the social division of labour depends not only on material incentives but also on expected satisfaction of a higher kind. In that case a woman, and especially a mother is confronted with adifficult decision to reconcile not only her own aims with those of the society but also with the aims and needs of the family. From the above line of thought a conclusion can be drawn, that the volume of women's work is conditioned by many factors. In that sense the phenomenon of female employment is an integral process, connected with all the aspects of the social and economic life.
The social and economic premises of the vocational women's work